26P Transforming growth factor-β makes the key characteristics of the proteome CD133- differentiated cells closer to CD133+ cancer stem cells of glioblastoma. (15th December 2019) - Zaitsev, S; Shevchenko, V; Arnotskaya, N; Lyakhova, I A; Khotimchenko, Y; Bryukhovetskiy, I S
Abstract: Background: Invasive growth of glioblastoma multiforme (GBM) is associated with CD133 + cancer stem cells (CSCs) and differentiated CD133- glioblastoma cells (DGCs) formed under the influence of transforming growth factor (TGF-β). The aim of the study was a comparison of CD133+ CSCs and CD133- DGCs proteomes stimulated by TGFβ. Methods: The human GBM U87MG cell line was cultured with a set of growth factors to obtain CSCs. CSCs were extracted through magnetic-activated cell sorting based on the expression of 133 cluster of differentiation; CD133- DGCs were used as a control. Differentiated glioblastoma cells (CD133- DGCs) were stimulated of TGF-β1. Highperformance liquid chromatography-mass spectrometry (HPLC-MS) was used for proteome analysis. Results: 589 proteins that significantly changed expression in CD133+ CSCs compared to (P < 0.05) CD133- DGCs were identified. Bioinformatics analysis revealed that 134 proteins belong to 15 signaling pathways. 14 proteins involved in signaling cascades associated with the interaction between CSCs and the ECM have been upregulated more than 2 times. 4 proteins responsible for activating this signaling cascades have also been upregulated more than 2 times. COL6A1 and LAMB1 in CD133+ CSCs have increased more than 8 times, and metalloprotease LOXL2 more than 9 times compared to CD133- DGCs. Stimulation with TGF-β have increased motility, inhibited proliferation and caused the transformation of the CD133- DGCs proteome through inhibition of the synthesis of adhesive E-cadherin, occludin and claudine-1, increasing production of migratory N-cadherin, vimentin, vitronectin, proteins of the actin-myosin complex, matrix metalloproteinases MMP2, MMP9, MMP14, ADAMTS1. At the same time, 13 proteins of the signaling pathway of the receptor interaction with the ECM: CD44, HMMR, COL1A2, COL6A1, COL6A3, FN1, LAMB1, LAMC1, ITGA2, ITGA5, ITGAV, ITGB1, ITGB3 and 3 proteins FERMT2, HDAC2, FBN1 activating this signaling pathway in CD133- DGCs have reached values comparable to CD133+ CSCs. Conclusion: TGF-β enhances expression of the ECM-receptor interaction signaling pathway proteins in CD133- DGCs differentiated GBM cells to the level of cancer CD133+ stem cells. Legal entity responsible for the study: Far Eastern Federal University. Funding: Ministry of Science and Higher Education of the Russian Federation (grant no. 14.584.21.0027; ID: RFMEFI58417X0027). Disclosure: All authors have declared no conflicts of interest.